Geo-Economic Aspects of Population Problem in Nepal - Shrestha, S. H. (Himalayan Review, 2011)
Not available. Key words: Geo-economic; Population; Human resources The Himalayan Review Vol. 11, 1979 Page: 16-26 Uploaded Date: April 3, 2011